Hepcidin knockout mice spontaneously develop chronic pancreatitis owing to cytoplasmic iron overload in acinar cells. Issue 1 (1st December 2016) - Lunova, Mariia; Schwarz, Peggy; Nuraldeen, Renwar; Levada, Kateryna; Kuscuoglu, Deniz; Stützle, Michael; Vujić Spasić, Maja; Haybaeck, Johannes; Ruchala, Piotr; Jirsa, Milan; Deschemin, Jean‐Christophe; Vaulont, Sophie; et al.
Abstract: Iron is both an essential and a potentially toxic element, and its systemic homeostasis is controlled by the iron hormone hepcidin. Hepcidin binds to the cellular iron exporter ferroportin, causes its degradation, and thereby diminishes iron uptake from the intestine and the release of iron from macrophages. Given that hepcidin‐resistant ferroportin mutant mice show exocrine pancreas dysfunction, we analysed pancreata of aging hepcidin knockout (KO) mice. Hepcidin and Hfe KO mice were compared with wild‐type (WT) mice kept on standard or iron‐rich diets. Twelve‐month‐old hepcidin KO mice were subjected to daily minihepcidin PR73 treatment for 1 week. Six‐month‐old hepcidin KO mice showed cytoplasmic acinar iron overload and mild pancreatitis, together with elevated expression of the iron uptake mediators DMT1 and Zip14. Acinar atrophy, massive macrophage infiltration, fatty changes and pancreas fibrosis were noted in 1‐year‐old hepcidin KO mice. As an underlying mechanism, 6‐month‐old hepcidin KO mice showed increased pancreatic oxidative stress, with elevated DNA damage, apoptosis and activated nuclear factor‐κB (NF‐κB) signalling. Neither iron overload nor pancreatic damage was observed in WT mice fed iron‐rich diet or in Hfe KO mice. Minihepcidin application to hepcidin KO mice led to an improvement in general health status and to iron redistribution from acinar cells to macrophages. It also resulted in decreased NF‐κB activation and reduced DNA damage. In conclusion, loss of hepcidin signalling in mice leads to iron overload‐induced chronic pancreatitis that is not seen in situations with less severe iron accumulation. The observed tissue injury can be reversed by hepcidin supplementation. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.